The reality of leadership among leaders of government secondary schools in Jeddah from the point of view of the teachers - Al-Zahrani, Mastourah Abdulrahim (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the reality of entrepreneurial leadership among the leaders of public high schools in Jeddah from the point of view of the female teachers, and to diagnose the reality of the dimensions of entrepreneurial leadership (creativity, initiative, investment of opportunities, tendency to take risks). The survey descriptive approach was used, and the questionnaire was used as a main tool for collecting information, and it was applied to a random sample of (366) female teachers, and the data was processed using the statistical package (spss) program.The study concluded that the degree of pioneering leadership practice at the level of the combined dimensions of secondary school leaders obtained an overall average (3.08 out of 5), i.e. with a degree (medium), and at the level of dimensions; the initiative dimension got the highest average (3.32), then the creativity dimension with an average of (3.26), and thirdly, the investment of opportunities with an average of (3.19), all with a degree of practice (medium), and finally; the "risk propensity" dimension, with a mean (2.55) and a degree of exercise (low).The results also showed that there were statistically significant differences in the degree of pioneering leadership practice due to the educational qualification variable in favor of the (bachelor’s) holders, and according to the years of service variable, and in favor of the female teachers (more than 10 years).Based on the results, the researcher presented a set of recommendations, the most important of which are: Organizing training courses held by specialists for school leaders in order to develop the dimensions of entrepreneurial leadership, and benefiting from the 2030 strategy in developing the skills and dimensions of entrepreneurial leadership, and linking the evaluation of school leaders’ performance to their implementation of entrepreneurial leadership and showing this in the evaluation report.
Keywords: reality; dimensions of entrepreneurial leadership; high school leaders; the city of Jeddah; teachers' point of view